Using Artificial Intelligence to Address Mental Health Inequalities in Low-Income, Urban Youth in North West England: A Digital Health Promotion Intervention - Andi Stanescu (BJPsych Open)
Aims: This study aims to design and implement a digital health promotion intervention aimed at reducing mental health inequalities among low-income, urban youth in North West England. The intervention is grounded in the hypothesis that a combined approach – incorporating peer mentorship, digital technology, and community-driven initiatives – will enhance mental health awareness, reduce stigma, and increase engagement with mental health services in this vulnerable population.